“Library Is A Growing Organism”: Aplikasinya dalam Masyarakat Informasi - C. Esmi Triningsih (Indonesian Journal of Library and Information Science, 2023)
The library is a vehicle for information resources which is expected to help educate the nation's life. As an organism that continues to grow, libraries will continue to grow and innovate in providing services to the community of users. Advances in information technology are seen as having the most influence on library development. This is because information technology affects all aspects of activities in the library. Library components also grow and develop dynamically, namely collections, librarians, users, and physical infrastructure such as buildings, furniture and equipment. The library's strategy in order to survive and develop in the midst of society is, first of all, to re-establish library and community relations which are full of dynamics. Second, to manage the library with good and correct management so that it can play a role in providing information both at the local and global levels. in network form. The development of libraries in society is a barometer of the development of the information society. The concrete thing is that people need the availability and ease of access to information. In an information society, information has become an inseparable part of every aspect of people's lives.